Using the balanced scorecard as a tool for project risk management - a case study in Al Kindi Company for the Production of Vaccines and Veterinary Medicines. - Al-Kawaz, Salah Mahdi Jawad; Ali Baig, Tayseer Jawad Kazem (Al-Ghary Journal of Economic and Administrative Sciences, 2022)
The research aims to review the literature to show the relationship and association between each of the balanced scorecard and enterprise risk management to reach performance measurement and risk management through the balanced scorecard and use the risk perspective to identify and measure the risks facing economic units. The researchers used a set of important measures in this perspective to measure the most important The risks experienced by the company, the research sample, and the researchers concluded a set of conclusions, most notably the use of the balanced scorecard as a tool for enterprise risk management, as there is a relationship between both variables in many goals, elements, and dimensions. The updated enterprise Risk Management Regulatory Authority for the year 2017, in conjunction with the Balanced Scorecard, to enhance the quality of the company’s performance and manage its risks appropriately